Muscular tissue desaturation and pneumonia in patients receiving lung cancer surgery: a cohort study. Issue 1 (5th January 2023) - Zhao, Wei; Zhang, Caijuan; Mu, Dongliang; Cui, Fan; Jia, Huiqun
Abstract: Background: Post-operative pneumonia (POP) is a common complication of lung cancer surgery, and muscular tissue oxygenation is a root cause of post-operative complications. However, the association between muscular tissue desaturation and POP in patients receiving lung cancer surgery has not been specifically studied. This study aimed to investigate the potential use of intra-operative muscular tissue desaturation as a predictor of POP in patients undergoing lung cancer surgery. Methods: This cohort study enrolled patients (≥55 years) who had undergone lobectomy with one-lung ventilation. Muscular tissue oxygen saturation (SmtO2 ) was monitored in the forearm (over the brachioradialis muscle) and upper thigh (over the quadriceps) using a tissue oximeter. The minimum SmtO2 was the lowest intra-operative measurement at any time point. Muscular tissue desaturation was defined as a minimum baseline SmtO2 of <80% for >15 s. The area under or above the threshold was the product of the magnitude and time of desaturation. The primary outcome was the association between intra-operative muscular tissue desaturation and POP within seven post-operative days using multivariable logistic regression. The secondary outcome was the correlation between SmtO2 in the forearm and that in the thigh. Results: We enrolled 174 patients. The overall incidence of muscular desaturation (defined as SmtO2 < 80% in the forearm at baseline) was approximately 47.1% (82/174). The patients with muscular desaturation had a higher incidence of pneumonia than those without desaturation (28.0% [23/82] vs. 12.0% [11/92]; P  = 0.008). The multivariable analysis revealed that muscular desaturation was associated with an increased risk of pneumonia (odds ratio: 2.995, 95% confidence interval: 1.080–8.310, P  = 0.035) after adjusting for age, American Society of Anesthesiologists status, Assess Respiratory Risk in Surgical Patients in Catalonia score, smoking, use of peripheral nerve block, propofol, and study center. Conclusion: Muscular tissue desaturation, defined as a baseline SmtO2 < 80% in the forearm, may be associated with an increased risk of POP. Trial registration: No. ChiCTR-ROC-17012627.